Հայկական հնագույն բարձրաշխարհիկ կահույքը - Գյուլխասյան, Բագրատ
Furniture is an integral part of any living quarter. It always emphasized social status and the taste of the owner. History of furniture goes deep into centuries showing the development of cultural and social life of different nations and civilizations. Armenian secular furniture is very interesting. It appears to us mainly by several artifacts found during archaeological excavations in the ancient Armenian cities and by means of historical evidences. Ancient Armenian furniture is known from the Late Bronze Age, from Urartu and the Hellenistic period. Armenian furniture was evolved under the influence of oriental ancient cultures, partly borrowed traditions, forms and aesthetics. Мебель является неотъемлемой частью любого жилого помещения. Она всегда подчеркивала социальный статус и вкус хозяина. История мебели уходит в глубь веков, показывает развитие культурной и светской жизни разных народов и цивилизаций. Очень интересна армянская светская мебель, которая представляется нам главным образом некоторыми артефактами, найденными во время археологических раскопок в древнейших армянских городах и посредствам исторических свидетельств. Древнейшая мебель из Армении известна от поздней бронзы, из Урарту и эллинистического периода. Армянская мебель развивалась под влиянием восточных древних культур, отчасти заимствовав традиции, формы и эстетику.
Keywords: Արվեստ; Կահույքագործություն